Growth and Yield Response of Caisim Plant (Brassica Juncea L.) to Treatment of Growing Media Type and AB Mix Solution Concentration in Floating System Hydroponic Technology - Lestari, Ayudini; Suciaty, Tety; Setya Wahyu Atmaja, Ida (Ann Publisher, 2024)
This research aims to determine the effect of AB mix solution and planting media on the growth and yield of caisim (Brassica juncea L.) in a floating hydroponic system. This research was carried out from March 2022 to April 2022 at the CV Green Vest Hydroponic Garden located in Cirebon City, West Java, at an altitude of 4 m above sea level. The research used the Split Plot Design method, the main factor AB mix concentration consisting of 3 levels (10, 14, 18 ml/l) and the second factor as a subplot, namely the planting medium consisting of 3 levels (cocopeat, sawdust, zeolite). Observations were made on plant height, number of leaves, root length, root volume, fresh weight per plant, and fresh weight per plot. The results showed that there was an interaction between the concentration of AB mix and planting media on plant height at 7 DAP, number of leaves at 7, 14, and 21 DAP, root length at 21 DAP, root volume at 14 DAP and 21 DAP, fresh weight per plant, and fresh weight per plot. The AB mix concentration treatment had an independent effect on plant height at 14 and 21 DAP, root length at 7 and 14 DAP, and root volume at 7 DAP. Meanwhile, the planting media treatment had an independent effect on plant height at 14 and 21 DAP, root length at 7 and 14 DAP, and root volume at 7 DAP. The treatment of cocopeat planting media and AB mix concentration of 18 ml/l gave the highest average fresh weight per plot, 4.01 kg.